Something to Believe: A Theological Perspective on Infant Baptism - Forde, Gerhard O. 1927-2005 (1993)
Our know-it-alls, the new spirits, assert that faith alone saves and that works and external things contribute nothing to this end. We answer: It is true, nothing that is in us does it but faith, as we shall hear later on. But these leaders of the blind are unwilling to see that faith must have something to believe—something to which it may cling and upon which it may stand. Thus faith clings to the water and believes it to be Baptism in which there is sheer salvation and life, not through the water, as we have sufficiently stated, but through its incorporation with God's Word and ordinance and the joining of his name to it. When I believe this, what else is it but believing in God as the one who has implanted his Word in this external ordinance and offered it to us so that we may grasp the treasure it contains? (Martin Luther, Large Catechism)1